Australia as a destination for Latin American doctoral candidates: Four personal reflections. Issue 1 (1st March 2020) - Bendrups, Dan; Diaz-Gasca, Sebastian; Ortiz, Gabriela Constanza Martinez; Sanchez, Perla Guarneros; Mena-Maldonado, Elisa
Universities are important drivers for transnational migration to Australia, especially for students who are economically mobile, or who might be seeking to convert a transitory study experience into a more permanent migratory one. The economic growth experienced in a number of Latin American countries in the twenty-first century introduced new cohorts of Latin American students into Australian tertiary education institutions, including some from countries that may have had minimal prior presence in Australia. This includes students working towards research degrees. This article presents the autoethnographic accounts of four doctoral candidates from Latin America studying in Australia. It considers their motivations for undertaking graduate research, and the factors that brought them to choose Australia as a study destination, and the benefits and challenges they have experienced in coming here. While the candidates are all from different research fields, their experiences reveal commonalities around three key themes: opportunity, safe exploration and the role of family in enabling decisions about transnational doctoral education.